Histological changes in the aortic valve after balloon dilatation: evidence for a delayed healing process. Issue 6 (June 1992) - van den Brand, M; Essed, C E; Di Mario, C; Plante, S; Mochtar, B; de Feyter, P J; Suryapranata, H; Serruys, P W
Abstract : OBJECTIVE--To investigate whether balloon dilatation of the aortic valve induces long-term macroscopic or histological changes or both to explain the restenosis process. DESIGN--Prospective study of 39 consecutive patients. Sixteen later (mean (SD) 12 (10) months) required operation. This non-randomised subgroup was compared with 10 patients who had aortic valve replacement without prior dilatation. SETTING--University cardiology and cardiac surgery centre and pathology department. PATIENTS--16 patients who had aortic valve replacement because of failure of or restenosis after balloon dilatation of the aortic valve. Twelve resected valves were examined. INTERVENTIONS--Percutaneous balloon dilatation of the aortic valve (maximal balloon size: trefoil 3 x 12 mm balloon or bifoil 2 x 19 mm balloon) and surgical inspection before excision of the aortic valve leaflets during open-chest aortic valve replacement. Fixation, decalcification, and staining for histology. MAIN OUTCOME MEASURES--Presence of long-term pathological changes in the resected valve and their relation to restenosis after balloon dilatation. RESULTS--Macroscopically the previously dilated valves were indistinguishable from valves from the patients who had valve replacement only. Microscopically, the dilated aortic valves showed areas of young scar tissue that were not seen in a control group of surgically excised stenotic aortic valves. This persistent scarring reaction was seen around small tears or lacerations of the collagenous valve stroma, fractures in calcified areas, and splits in commissures. Young scar tissue without collagenisation was still present 24 months after dilatation. CONCLUSION--Organisation and collagenisation of scar tissue develops slowly after balloon dilatation of the aortic valve. This prolonged scarring reaction may explain the late development of restenosis in some patients.